Effect of doping profile and the work function variation on performance of double-gate TFET - Elgamal, Muhammad; Sinjab, Aya; Fedawy, Mostafa; Shaker, Ahmed (International Journal of Integrated Engineering, 2019)
Abstract Tunnel Field Effect Transistor (TFET) can be considered as one of the promising transistors because it can switch ON and OFF at lower voltages than the operation voltage of the metal oxide semiconductor field effect transistor (MOSFET). This paper presents the effects of gate electrode work function and the doping profile terminating within and outside the drain on the ambipolar current, the ION/IOFF ratio, and the subthreshold swing. The results show that, Gaussian doping profile terminating within the drain is the most promising for on/off ratio. All the simulations and results have been performed and obtained with the help of ATLAS device simulator (Silvaco) and MATLAB.